Crime Rates in India: A Trend Analysis. (December 2015) - Ansari, Sami; Verma, Arvind; Dadkhah, Kamran M.
This study presents the trend analyses of police-recorded crime data in India. We demonstrate the long-term trends of serious violent and property crimes and examine whether the crime trend in India follows the global crime trend, especially the declining trend in the United States and West European countries. By examining the peaks, troughs, and turning points, this study examines the similarities and differences in long-term trends between different crime types. The data for our study are drawn from Crime in India, an annual publication by the National Crime Record Bureau of India. The results suggest that rates of murder, robbery, burglary, theft, and rioting follow declining trends, while rates of rape show an increasing trend between 1971 and 2011. The homicide trend is the only crime category following the global crime trend. While recognizing the universal and India-specific limitations of the police-recorded crime data, we want readers to consider the findings of the study with caution. We strongly recommend that India establish a national crime victimization survey and regularly participate in the International Crime Victimization Survey.